2017
DOI: 10.1002/jcp.25896
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of MGMT promoter methylation in glioblastoma: A meta‐analysis of clinical trials

Abstract: The DNA repair protein O6-Methylguanine-DNA methyltransferase (MGMT) is suggested to be associated with resistance to alkylating agents such as Temozolomide which is being used in treatment of patients with glioblastoma (GBM). Therefore, we evaluated the associations between MGMT promoter methylation and prognosis of patients with glioblastoma (GBM).Data were extracted from publications in Embase, PubMed, and the Cochrane Library. Data on overall survival (OS), progression-free survival (PFS), and MGMT methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
179
3
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(202 citation statements)
references
References 47 publications
14
179
3
6
Order By: Relevance
“…This feature was associated with a better overall survival, 21.7 months after chemotherapy associated with radiotherapy, in comparison to 15.3 months for patients carrying non-methylated genotype (Stupp et al, 2009). More recently, a meta-analysis of 10 eligible studies, including the MGMT methylation status of more than four thousand subjects, confirmed that patients bearing this genotype present longer overall survival (Binabaj et al, 2018), emphasizing MGMT status as an independent indicator of a favorable prognosis. MGMT methylation could also be found in patient serum and strongly correlated with its presence in the tumor tissues (Fiano et al, 2014), suggesting that detection in blood samples could represent a re-DNA repair genes in astrocytoma 3 liable tool to predict response to TMZ treatment.…”
Section: Dna Repair Genes As Biomarkers Of Astrocytoma Aggressivenessmentioning
confidence: 91%
See 1 more Smart Citation
“…This feature was associated with a better overall survival, 21.7 months after chemotherapy associated with radiotherapy, in comparison to 15.3 months for patients carrying non-methylated genotype (Stupp et al, 2009). More recently, a meta-analysis of 10 eligible studies, including the MGMT methylation status of more than four thousand subjects, confirmed that patients bearing this genotype present longer overall survival (Binabaj et al, 2018), emphasizing MGMT status as an independent indicator of a favorable prognosis. MGMT methylation could also be found in patient serum and strongly correlated with its presence in the tumor tissues (Fiano et al, 2014), suggesting that detection in blood samples could represent a re-DNA repair genes in astrocytoma 3 liable tool to predict response to TMZ treatment.…”
Section: Dna Repair Genes As Biomarkers Of Astrocytoma Aggressivenessmentioning
confidence: 91%
“…DNA repair genes considered biomarkers* of GBM susceptility and/or progression Hegi et al, 2005;Hegi et al, 2008;Stupp et al, 2009;Binabaj et al, 2018. …”
mentioning
confidence: 99%
“…Thus, increased MGMT activity in tumour cells counteracts the cytotoxic damage induced by antitumour agents [10]. Since the initial research by Esteller et al [11], many studies have provided convincing evidence showing that glioma patients with decreased level of MGMT activity have longer overall survival (OS) and progression-free survival (reviewed in [12]). The decrease of MGMT activity in glioma cells is caused by epigenetic silencing of MGMT through hypermethylation of cytidine-phosphate-guanosine dinucleotides (CpG islands) in the promoter region, rather than mutations or deletions.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease of MGMT activity in glioma cells is caused by epigenetic silencing of MGMT through hypermethylation of cytidine-phosphate-guanosine dinucleotides (CpG islands) in the promoter region, rather than mutations or deletions. These findings led to the suggestion that the MGMT promoter methylation status could serve as a highly promising prognostic factor for malignant glioma patients [12,13]. However, several studies dealing with the MGMT methylation status in malignant glioma gave controversial results suggesting that the prognostic value of MGMT promoter methylation on GBM remains unclear [12,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…MGMT is a suicide repair protein which removes the O6-guanine adduct and allows for proper DNA repair 6 . Even with this information, targeting MGMT with both small molecule drugs and mimetics has been unsuccessful, and its expression does not always correlate with resistance to TMZ [7][8][9][10][11] . Therefore, new models of resistance need to be developed in order to better define molecular mechanisms of GBM resistance to TMZ.…”
Section: Introductionmentioning
confidence: 99%